Creek Internationalism in an Age of Revolution, 1763-1818 - Hill, James L., 1986- (Book collections on Project MUSE., 2022)
"This significant revisionist history of Creek diplomacy and power fills gaps within the broader study of the Atlantic World and early American history to show how Indigenous power thwarted European empires in North America"--